Diversity of Sub-Gingival Fluids Microbiota Compositions in Periodontitis and Rheumatoid Arthritis Patients: A Case-Control Study - Viranda Sutanti; Eko Suyanto; Mufidah Mufidah; Nia Kurnianingsih (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the diversity of microbiota in the sub-gingival fluids from periodontitis and rheumatoid arthritis (RA) patients and to know the relationship of microbiota abnormalities between periodontitis and RA. Material and Methods: Samples were collected from sub-gingival fluids of nine participants by swabbing technique. The participants were divided into 3 groups, namely the control (not periodontitis and RA), periodontitis, and RA. The total number of bacteria was calculated by using direct culture in serial dilution by applying the total plate count method. Isolation of microbiota was conducted by pour plates and incubated in an anaerobic jar. The bacterial diversity was performed by Simpson index and DNA Isolation. Results: There were differences in the concentration of sub-gingival fluids bacteria in the control group with the periodontitis and RA group. The microbiota composition profiles were different for each group. The bacterial isolate 4, 5 and 22 were found in all groups, while isolate 14 was assumed to be related to the metabolic pathway in microbiota abnormalities associated with disease progression. Conclusion: The Simpson index has a value >0.61 with high bacterial dominance; however, the diversity of microbiota is at a low level of diversity. We assumed that isolate 14 was associated with development of RA disease.